Pengaruh Struktur Aset, Ukuran Perusahaan, Pertumbuhan Perusahaan, Profitabilitas, dan Kebijakan Dividen terhadap Struktur Modal - Warsiman, Chrysan Kirana; Kurnia, Ratnawati (Universitas Multimedia Nusantara, 2014)
The objective of this research was to examine the effect of asset structure that measured by Asset Tangibility, firm size that measured by Total Assets, firm growth that measured by Asset Growth, profitability that measured by Profit Margin, and dividend policy that measured by Payout Ratio towards capital structure that measured by Long Term Debt to Equity Ratio. The samples in this study were 19 companies that listed in Bursa Efek Indonesia (BEI) consecutively as consumer goods industry sector and miscellaneous industry sector, published audited annual financial statement, published annual financial statement in Rupiah, generated positive income every year, and paid cash dividend every year in the research period (2010-2012). The sample in this study was determined based on purposive sampling. Data used in this study were secondary data, such as financial statements. Method of analysis data.used in this research was multiple linear regressions. The result of this study were (1) asset structure that measured by Ln Asset Tangibility had positive influence to capital structure; (2) firm size that measured by Ln Total Assets had positive influence to capital structure; (3) firm growth that measured by Ln Asset Growth had positive correlation and no influence to capital structure; (4) profitability that measured by Ln Profit Margin had positive correlation and no influence to capital structure; (5) dividend policy that measured by Payout Ratio had negative correlation and no influence to capital structure; and (6) asset structure that measured by Ln Asset Tangibility, firm size that measured by Ln Total Assets, firm growth that measured by Ln Asset Growth, profitability that measured by Ln Profit Margin, and dividend policy that measured by Payout Ratio had influence to capital structure simultaneously. Keywords : capital structure, asset structure, firm size, firm growth, profitability, dividend policy